Development of LEU-based Targets for 99Mo Production - SHEN Yijia;WU Yuxuan;LUO Zhifu (Journal of Isotopes, 2023)
One of the major isotopes used in nuclear medicine is 99mTc. 99mTc for medical purpose is a decay product of 99Mo, which is produced in research reactors from the fission of 235U. Uranium targets are being converted from highly enriched uranium (HEU) to low enriched uranium (LEU) to prevent nuclear proliferation. Advantages and disadvantages of various target designs are investigated and discussed along current disposal methods. In the present paper,some advice was also given for further exploration.